KAJIAN KERUSAKAN LINGKUNGAN TANAMAN PERTANIAN AKIBAT AKTIVITAS INDUSTRI PENGOLAHAN DOLOMIT DI KECAMATAN PANCENG KABUPATEN GRESIK - , Dini Atikawati; , Prof. Dr. Totok Gunawan, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The existence of dolomite processing industry in the Banyutengah Village, Panceng Subdistrict has a negative impact on the environment because it produces dust. The dust sticks on agricultural crops because the industry located around agricultural land. This study aims to: (1) examine the distribution of environmental damage of agricultural crops caused by dust from dolomite processing industry that cause environmental problems, (2) assess the environmental damage of agricultural crops caused by dust from dolomite processing industry, and (3) formulate environmental management strategies to control environmental damage of agricultural crops. This study uses observation method. Dust sampling was done with paying attention to the type of land use and distance from the industry. Agricultural crops sampling was done randomly. Fruit sampling was done with paying attention to the ripe fruit. Leaf sampling was done by observing the location of the leaf. The data analysis uses quantitative descriptive, spatial, and qualitative descriptive analysis. The results show that spread of dust on agricultural crops include Banyutengah, Campurejo, Pantenan, Ketanen, Dalegan, Waru Lor, Tlogosadang, and Sidokumpul Village. Agricultural crops which are at north, northwest, southwest and at a distance of 150-600 m from the industry, the leaf surface is covered by dust. The closer the crops distance from the industry, the lower the levels of chlorophyll and the farther the crops distance from the industry, the higher the levels of chlorophyll. The crops production decreased by 175,003 tonnes, with loss value 1.281.384.600 rupiah. The environmental management strategies includes A, B, and C environmental management strategies that are abiotic